(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
The first films introduced into market are around 1970, from then there are many new technologies are developed in preparation and also using polymers. From Natural to synthetic polymers each polymer has their advantages over one another. Various techniques in preparation of oral films such as solvent casting, semi-solid casting, hot-melt extrusion, solid dispersion extrusion and rolling to the modern techniques are developed from time to time. The most recent technique used is 3D printing which forms the films by forming layer on layer. In this literature along with polymers used, methods for preparing of films; approved drugs in orange books and present clinical trial studies were discussed.